Relationship Between Determinant Factors of Nurse Competency in Disaster Mitigation in 5 Community Health Centers in Ende - Budiana, Irwan; Patmawati, Try Ayu (MultiTech Publisher, 2024)
This research aims to determine factors related to nurse competency in disaster mitigation. This research is a descriptive analytical study with a cross sectional approach. The population in this study were all nurses in 5 Community Health Centers in Ende City. Sampling used a purposive sampling technique with an instrument in the form of a questionnaire. Data were processed using SPSS software with a multiple regression test. The research results showed that there was no relationship between age, gender, education level, length of service and participation in disaster training with nurses' competency in carrying out disaster mitigation. Meanwhile, the level of education and knowledge, length of service and attitudes and competence of nurses in disaster mitigation have a significant relationship